Vaccine-Induced Protection in Two Murine Models of Invasive Pulmonary Aspergillosis - Rayens, Emily; Rabacal, Whitney; Kang, S. Earl; Celia, Brandi N.; Momany, Michelle; Norris, Karen A. (Frontiers in Immunology, 2021)
Life-threatening, invasive fungal infections (IFIs) cause over 1.5 million deaths worldwide and are a major public health concern with high mortality rates even with medical treatment. Infections with the opportunistic fungal pathogen, Aspergillus fumigatus are among the most common. Despite the growing clinical need, there are no licensed vaccines for IFIs. Here we evaluated the immunogenicity and protective efficacy of an A. fumigatus recombinant protein vaccine candidate, AF.KEX1, in experimental murine models of drug-induced immunosuppression. Immunization of healthy mice with AF.KEX1 and adjuvant induced a robust immune response. Following AF.KEX1 or sham immunization, mice were immunosuppressed by treatment with either cortisone acetate or hydrocortisone and the calcineurin inhibitor, tacrolimus. To test vaccine efficacy, immunosuppressed mice were intranasally challenged with A. fumigatus conidia (Af293) and weight and body temperature were monitored for 10 days. At study termination, organism burden in the lungs was evaluated by quantitative PCR and Gomori’s methanamine silver staining. In both models of immunosuppression, AF.KEX1 vaccinated mice experienced decreased rates of mortality and significantly lower lung organism burden compared to non-vaccinated controls. The lung fungal burden was inversely correlated with the peak anti-AF.KEX1 IgG titer achieved following vaccination. These studies provide the basis for further evaluation of a novel vaccine strategy to protect individuals at risk of invasive aspergillosis due to immunosuppressive treatments.